Application of the TPACK Framework in Digital Assessment of Elementary School Students' Mathematical Communication Skills Based on Level of Self-Confidence - Vedianty, Adinda Syalsabilla Aida; Nurhayati, Dwi; Darmayanti, Rani; Lestari, Andika Setyo Budi (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
Integrating digital technology into elementary math education presents both opportunities and challenges, particularly in assessing students' mathematical communication skills. This study applies the Technological Pedagogical Content Knowledge (TPACK) framework to develop digital assessments for elementary students, focusing on varying self-confidence levels. Utilizing platforms like online portfolios and interactive simulations, the research evaluates students' abilities to communicate mathematical ideas through writing, visuals, and expressions. A mixed-methods approach combined quantitative data from self-confidence questionnaires and digital scores with qualitative data from digital portfolios and interviews. Fifth-grade students from the Assyfa Learning Center Pasuruan Foundation were grouped by self-confidence levels. Findings indicate a positive correlation between self-confidence and mathematical communication skills: students with high self-confidence met all indicators, while those with moderate and low self-confidence met fewer. Digital assessment tools enhanced evaluations and data richness. This study underscores the importance of integrating technology, pedagogy, and content knowledge in digital assessments and recommends ongoing teacher training and child-friendly platforms to boost equitable math assessment.